Effects of Antarctic Krill Euphausia superba Meal Inclusion on Growth, Body Color, and Composition of Large Yellow Croaker Larimichthys crocea. (27th August 2021) - Tang, Baojun; Zheng, Hanfeng; Wang, Shuaijie; Qin, Ganjing; Huang, Yanqing; Wang, Lumin
Abstract: The effects of Antarctic krill Euphausia superba meal inclusion in the diet of Large Yellow Croaker Larimichthys crocea were studied. Inclusion levels were 0.000, 4.125, 8.250, and 12.375% (control, KM4.125, KM8.250, and KM12.375, respectively), and groups of large‐sized fish (average body weight = 190.6 g) received these diets for 99 d. No significant differences were found in body length, body weight, and specific growth rate compared with the control group, but the KM4.125 and KM8.250 groups had significantly increased condition factors and hepatosomatic indices. The KM8.250 fish showed a significant increase in redness values in the dorsal skin, while the KM12.375 fish presented significantly higher yellowness in the ventral skin and tail fin. Addition of krill meal exerted no significant effect on whole‐body proximate composition. The KM8.250 group showed significantly higher lipid content and lower ash content, which differed from those of the KM12.375 group. Most of the amino acids in muscle and liver tissues remained unchanged compared to those in the control. The KM4.125 group showed significantly higher muscle proline, serine, and total functional amino acids, while the total amino acid content in KM12.375 fish significantly decreased. The results indicated that dietary inclusion of fish meal with up to 8.25% krill meal does not result in adverse effects on growth and body composition of large‐sized Large Yellow Croaker; however, addition of krill meal could improve skin coloration in these fish.